COMPUTER VISION TO SUPPORT PRE-SERVICE TEACHER MASTERY OF STUDENT CENTRE APPROACH - Hikmawan, Rizki (EDUTECH, 2021)
Various researcher state that to ensure student had the 4Cs competence is to use student-centered approach in the classroom. This further recognize the skills to create dynamic classroom as the core-skills of 21st teacher. To create such classroom, a teacher must be able to master the systematic and dynamic aspects of learning. It requires teacher to fully aware of every student activity. However, based on preliminary investigation, there two things that become obstacles, namely: (1) teacher had hard time giving full attention to whole classes due to non-coercion manner of student-centre approach, and (2) mastery of dynamic aspects in learning requires real experience which will certainly spend a lot of time. They need practical solutions that can help them master the core skill of 21st teacher. Therefore, we designed an application with image processing features (face detection, face recognition, and pose extraction) in order to help teachers to give full attention and provide positive reinforcement for every classroom participant. The research is done by RD Method, whereas application design uses SDLC method. The results are product in the form of software applications that are expected to accurately measure percentage student attention in the classroom. Product also present information as a basis for decision making to assist teacher in creating a dynamic classroom. In addition, we certainly hopeful that by using the product, prospective teachers can quickly adapt and apply the dynamic classroom.Â